Polylactide/cellulose nanocrystal nanocomposites: Efficient routes for nanofiber modification and effects of nanofiber chemistry on PLA reinforcement. (18th May 2015) - Spinella, Stephen; Lo Re, Giada; Liu, Bo; Dorgan, John; Habibi, Youssef; Leclère, Philippe; Raquez, Jean-Marie; Dubois, Philippe; Gross, Richard A.
Abstract: To improve the Heat Deflection Temperature of polylactide (PLA), nanocomposites were prepared with modified cellulose nanocrystals (CNCs) by melt blending. The preparation of acetate and lactate modified CNCs (AA- and LA-CNCs) was performed by a green one-pot dual acid (organic acid and HCl) method such that acid hydrolysis and Fischer Esterification occur in tandem. The degree of substitution for AA-CNCs and LA-CNCs, determined by FTIR, are 0.12 and 0.13, respectively. Relative to unmodified CNCs, esterification of CNC surfaces with lactate and acetate moieties resulted in a 40 °C increase in thermal stability. At 5 wt% loading of CNCs, LA-CNCs gave superior reinforcement below and above the glass temperature of PLA, corresponding to a 31% and 450% increase in PLA's storage modulus compared to neat PLA. An increase in PLA's heat deflection temperature by 10 °C and 20 °C was achieved by melt-blending PLA with 5 and 20% LA-CNCs, respectively. The above studies provide indirect evidence that LA-CNCs were best dispersed (lowest tendency to aggregate) in the PLA matrix. This hypothesis was confirmed through direct visualization using AFM. Thus, a simple modification strategy for CNCs was devised that enables the formation of PLA nanocomposites with high extents of nanofiber dispersion within the matrix. Furthermore, the dispersion of CNCs in PLA matrices is profoundly influenced by relatively small changes in the modification chemistry, in this case, appending lactate vs. acetate groups. Graphical abstract: Highlights: Lactate and acetate modified CNCs were produced by a one-pot procedure. PLA/CNC nanocomposites were produced by direct melt blending. Lactate CNCs lead to large increases in the storage modulus above and below the T g of PLA. A 20 wt% loading of lactate-CNC's resulted in a 20° increase in PLA's heat deflection temperature. AFM showed that lactate CNCs had the best dispersion in PLA when compared to nanocomposites with acetate and unmodified CNCs.